ESTUDO DE CASO COM PACIENTE COM EMBOLIA E TROMBOSE DA ARTÉRIA ILÍACA: UM RELATO DE EXPERIÊNCIA - Rosanelli, Cleci L. S. P.; Grimm, Julia Y.; Costa, lizangela A. d.; Feistel, Eliane; Santoni, Michele; Morais, Cheila L. O. (Salão do Conhecimento, 2013)
Resumo